Peningkatkan Higher Order Thinking Skills (HOTS) melalui Penerapan Model Pembelajaran Berbasis Case Method - Ekasari, Novita; Octavia, Ade; Sriayudha, Yayuk; Siregar, Ade Perdana (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
In the learning process, complex problems are not only at the level of achievement of students' perseverance. Achievement in creating quality human resources is a priority goal for educational institutions by creating graduates who have positive values and character so that they can stimulate productivity in students. Learning methods with the aim of improving Higher Order Thinking Skills (HOTS) are considered to be able to provide solutions in learning by overcoming global problems. Project-based learning means experience in the form of reality where attitudes and skills become knowledge construction as a basis for its application. The case method can be a recommendation in learning by reducing errors in theory and practice, which is the use of the right model for the success of project based learning. This research aims to study the effect of implementing project based learning using the case method as an effort to improve Higher Order Thinking Skills (HOTS). This research is descriptive research using qualitative analysis, where the data collection process is based on interviews and observations in the learning process of international business courses. This research has 2 types of variables, namely independent variables and dependent variables. The independent variable in this research is project-based learning, while the dependent variable in this research is Higher Order Thinking Skills (HOTS) with indicators covering the ability to combine concept sharing, interpretation, problem solving, problem solving strategies, discovery of new methods, argumentation and decision making. The application of project-based learning using the case method in international business courses has increased Higher Order Thinking Skills (HOTS) so that students can analyze and make decisions according to phenomena in conditions covering the current global environment.